Enhancing Transparency and Trust through Effective Financial Statement Audits - Anjani, Putri (Advances in Managerial Auditing Research, 2023)
Purpose: This study explores the critical role of financial statement audits in increasing transparency and trust in organizations. This research examines the audit process and its effectiveness and how audits can reduce information asymmetry, increase stakeholder trust, and ensure financial reporting integrity. Research Design and Methodology: This research utilizes an interdisciplinary literature review combining insights from finance, economics, psychology, and computer science. This approach helps in more thoroughly understanding the audit process and outcomes. The literature review identified key audit challenges, such as the complexity of financial transactions, regulatory changes, and technological advancements. Findings and Discussion: The results show that an effective financial statement audit can significantly reduce information asymmetry between management and external stakeholders, increase investor confidence, and strengthen market credibility. Auditors' main challenges include the complexity of financial transactions and the evolution of regulations. However, by capitalizing on technological innovations and regulatory changes, auditors can improve audit quality. Implications: The findings of this study have implications for audit policy and practice. Improving audit relevance and quality requires interdisciplinary collaboration and continuous innovation in audit methods. This study recommends that future research focus on refining audit techniques to address emerging risks and encourage higher standards of transparency in financial reporting.